LITERACY AND CHALLENGES OF THE 21ST CENTURY THROUGH INTEGRATIVE THEMATIC LEARNING AT STATE PRIMARY SCHOOL KUTA BAKME BANDA ACEH - Maharani; Tiara Nabila; Tamara Fitriyani; Yarda Safardin; Hamdani (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses a descriptive qualitative research method,namely research based on phenomena that occurred in one case at SDNegeri Kuta Bakme. Based on the facts seen in these schools, teachersstill use old or potential methods in the learning process through literacy,because teachers in these schools rarely have digital competence. Theresearcher observed the learning carried out by Kuta Bakme StateElementary School teachers that 21st century learning through literacyreally provides opportunities for teacher creativity in the active learningprocess. Through this research method, it shows that digital competencemust be possessed by a teacher to present the latest content in learning21st century through literacy. Digital competency is a person's ability touse and understand information technology effectively, including skillsin using hardware, software, the internet, as well as the ability to search,evaluate and utilize information from various digital sources. .Digitalcompetence shows the use of information and communication technologybased on pedagogical principles by being aware of the consequences thatarise or occur because of something for education. Digital competencyincludes mastering information and communication, creating learningcontent, and solving educational problems.